Untangling the relationship between bempedoic acid and gout: results from a systematic literature review - Alunno, Alessia; Carubbi, Francesco; Campanozzi, Elena; Bellisario, Federico; Schoones, Jan W.; Mariani, Francesco Maria; Di Ruscio, Evy; Altieri, Piera; Ferri, Claudio (Frontiers in Cardiovascular Medicine, 2023)
Background: Bempedoic acid (BA) is a small-molecule first-in-class of inhibitor of ATP citrate lyase that significantly lowers low-density lipoproteins cholesterol (LDL-c) in statin-intolerant and inadequate responders. Increased serum uric acid (SUA) levels and gout incidence have been described in BA-treated patients. The aim of this systematic review was to investigate the safety of BA regarding SUA levels and gout in randomised controlled trials (RCTs).Methods: A search on 7 databases was performed from inception to May 4, 2023. RCTs of BA monotherapy or combination with other lipid-lowering treatment (LLT) in patients with increased LDL-c were included. Dual data extraction was performed with disagreements resolved through consensus. Due to the methodological purpose of this review risk-of-bias assessment of studies was not performed.Results: 6 Phase 3 RCTs (N=17'975 patients of which 9'635 received BA) 9 Phase 2 RCTs (N= 362 patients of which 170 received BA) and an open-label extension of a Phase 3 RCT were included. Gout and/or hyperuricemia were not mentioned as exclusion criteria, previous/current use of urate-lowering therapies (ULT) and/or colchicine and/or dietary patterns were not reported. Phase 3 RCTs: 2 studies specified the number of patients experiencing hyperuricemia over the study period (BA: 4.9-11%; placebo: 1.9-5.6%) and the effect size was significant only in 1 study (OR=2.0, 95% CI 1.8-2.3). Four RCTs reported a higher incidence of gout in the BA arm however, when we calculated the effect size, it was small and often not significant. Two studies reported 0 cases of gout. The paucity of information about SUA levels at baseline and/or at the end of follow-up do not allow us to quantify the effect sizes for BA-induced SUA elevation. Data on gout from Phase 2 RCTs is scant. This is a provisional file, not the final typeset article Conclusions: Data from phase 2 and 3 RCTs do not allow for confirming a clear association between BA and gout. It is conceivable that a careful assessment of SUA levels/history of gout at baseline and the concomitant use of urate-lowering agents may be instrumental to minimise the risk of new-onset gout/gout flares in patients treated with BA.